Analisis Cost-Benefit Terapi Simvastatin dengan Atorvastatin pada Pasien Dislipidemia di Apotek 71 Kota Kediri dengan Pendekatan Human Capital Method - Prasetyawan, Fendy; Saristiana, Yuneka; Mildawati, Ratna; Fadel, Muhammad Nurul; Besan, Emma Jayanti; Astutik, Widhi; Arifin, Chandra; Rofiq, Abd; Rhomah, Eka Hayati (Fakultas Ekonomi Universitas KH. A. Wahab Hasbullah, 2025)
This study aims to analyze the cost-benefit of simvastatin therapy compared to atorvastatin in dyslipidemia patients at Apotek 71 Kediri City using the Human Capital Method. Using a cross-sectional study design, this study analyzed 60 patients (30 simvastatin users, 30 atorvastatin users). Productivity loss data was collected through a patient self-report questionnaire and valued monetarily using the assumption of a uniform daily wage. Results showed that direct costs of simvastatin were lower (IDR 75,000/month) than atorvastatin (IDR 210,000/month), but lost productivity in the simvastatin group was higher (IDR 384,000) than atorvastatin (IDR 180,000). The Net Benefit value of simvastatin therapy was -Rp 39,000 with a Benefit Cost Ratio (BCR) of 0.91, while atorvastatin produced a Net Benefit of +Rp 210,000 with a BCR of 1.54. The difference in Net Benefit was statistically significant based on an independent t-test (p=0.002). Thus, atorvastatin is more economically efficient than simvastatin because it provides higher productivity benefits despite higher direct costs.